Photochemical formation of a fluorescent thymidine-pterin adduct in DNA - Estébanez, Sandra (2018)
The photochemistry of the DNA biomacromolecule is an issue of paramount importance as it is part of the etiology of skin cancer development, being ultraviolet sunlight radiation the most relevant environmental carcinogen. Herein, we demonstrate the potential of pterin, an endogenous compound, to form covalent adduct under UVA irradiation with a short thymine oligomer as well as with the whole DNA polymer. Our approach is based on the spectroscopic features of pterin, which allow, by monitoring specific absorption or emission wavelengths, the following-up of the covalent binding. The results are confirmed by HPLC coupled with mass spectrometry, revealing the attachment of one or two pterin units to the homothymine 5-mer oligonucleotide. Altogether the findings point toward the role of pterin as endogenous sensitizer and genotoxic compound.